2003
DOI: 10.1111/j.1600-0412.2004.00285.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of body mass index on the prevalence of complications after vaginal and abdominal hysterectomy

Abstract: Vaginal and abdominal hysterectomy have a significant risk of complications, but obese patients did not experience an increased risk of serious morbidity compared to normal weight women. Obesity per se is not a contraindication of vaginal or abdominal hysterectomy in otherwise healthy women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…Fifty‐six studies examined incidence of post‐surgical infections and complications in patients who were obese, compared with those who were normal weight. Fifty‐four of the studies reported increased complications associated with obesity . Thirteen of 56 of the studies reported higher incidence of infection, 20 of the 56 found an increase in surgical site infections, six of the studies found higher degrees of deep sternal wound infections and 14 studies reported other types of post‐operative complications such as re‐hospitalization.…”
Section: Resultsmentioning
confidence: 99%
“…Fifty‐six studies examined incidence of post‐surgical infections and complications in patients who were obese, compared with those who were normal weight. Fifty‐four of the studies reported increased complications associated with obesity . Thirteen of 56 of the studies reported higher incidence of infection, 20 of the 56 found an increase in surgical site infections, six of the studies found higher degrees of deep sternal wound infections and 14 studies reported other types of post‐operative complications such as re‐hospitalization.…”
Section: Resultsmentioning
confidence: 99%
“…Others studies showed opposing results. A study that evaluated complications after hysterectomy showed no associations between BMI and risk of infections ( 31 ). In another study, the risk of infections was elevated among women with BMI < 20 kg/m2, who underwent laparoscopic surgery ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…7,13,27,34,40,43,47 Obese patients have also been reported to have worse outcomes after blunt trauma. This includes reports in the gynecological, orthopedic, cardiovascular, urological, and transplantation literature.…”
Section: Prevalence Of Obesity In Patients Undergoing Elective Thoracmentioning
confidence: 99%